Crystal structure of 2-amino-4-(2-fluoro-4-(trifluoromethyl)phenyl)-9-methoxy-1,4,5,6-tetrahydrobenzo[h]quinazolin-3-ium chloride, C20H18ClF4N3O - Li Wen-Xuan; Meng Qing-Guo; Hou Gui-Ge; Liu Yong-Jun; Zhang Meng (Zeitschrift für Kristallographie - New Crystal Structures)
C20H18ClF4N3O, monoclinic, P21/c (no. 14), a = 9.6123(7) Å, b = 11.8692(7) Å, c = 16.9510(12) Å, β = 104.798(7)∘, V = 1869.8(2) Å3, Z = 4, Rgt(F) = 0.0444, wRref(F2) = 0.1043, T = 293 K.